PENGATURAN RETUR BARANG OLEH PIHAK EKSPEDISI PADA APLIKASI SHOPEE PERSPEKTIF MAQASHID SYARI’AH - Afifah, Fauziyyah; Hidayat, Rahmat (Universitas Muhammadiyah Ponorogo, 2024)
The popularity of online buying and selling transactions on the Shopee app allows you to shop without having to visit a store or market centre. However, this cannot be separated from the problem. Some of these issues include unsuccessful courier delivery due to damaged products, inaccurate address, and inability to reach the buyer during the delivery process. Failed delivery results in the products being returned to the seller by the expedition in accordance with Shopee policies. Objective This research demonstrates how to give legal protection for customers. Return of goods by the expedition party via the Shopee app. And to find out Consumer protection procedures for the return of items by the expedition party on the Shopee application, reviewed from maqashid shariah. This study seeks to determine the manner of control of unilateral returns of items by expeditions, as well as the idea of consumer protection, from a Maqashid Syari’ah perspective. The research methodology is empirical law with a living case studies, statute, and conceptual approach. Results This study explains that the courier violated the principles of good faith and default as regulated in Article 1338 paragraph (3) of the Civil Code and Article 7 letter an of the Consumer Protection Law, allowing consumers who have been harmed to seek compensation for the costs of ordering goods from Shopee, a business actor that provides marketplace services. Consumer protection against material losses is the application of according to the principle of Hifz al-Mal (property protection), Shopee is required to give a guarantee of compensation for the return of items by the expedition.